Ensino médio articulado à educação profissional no IFMA: uma avaliação política da política - Pereira Filho, Francisco de Assis (2017)
The study deals with the political evaluation of the Basic Education Policy articulated to Professional Education, specifically at the Federal Institute of Education, Science and Technology of Maranhão (IFMA). It elaborates a historical retrospective of the public policies in relation to the basic education, having as axis guiding the structural duality existing between the formation of propedeutic character directed to the elites and the instrumental education provided to the popular classes. It contextualizes the foundations of omnilateral and polytechnic education, and of the unitary school of Marx and Gramsci. It characterizes the conceptions and principles that determined the formulation of this Policy in IFMA. It is based on a qualitative research that uses bibliographical and documentary research, based on several legal documents (laws, decrees, mainly Decrees nº 2.208/1997 and 5.154/2004) and on institutional documents of the IFMA (pedagogical project, Development plan, regiments, etc.). According to the data analyzed, the articulation between the High School and Professional Education in the IFMA presents limitations in its execution, mainly in relation to teacher training, lack of laboratories and contingency of resources. It complements that even with the limitation of these inputs, the IFMA through its guidelines needs to invest heavily in the qualification of the teaching staff for the pedagogical practice, based on the polytechnics and omnilaterality aiming at the training of its students.